Self‐organizing market structures, system dynamics, and urn theory. Issue 4 (1st March 2013) - Buendía, Fernando
Abstract Using data from Fortune Magazine's 500 American largest corporations from 1955 to 2010, this article shows that firm sizes at national and industrial level are highly skew but not Zipf‐distributed. It also argues that, while self‐organizing industrial structures of this kind are due to increasing returns and hard to describe with conventional theories, system dynamics and urn theory are equipped with adequate tools to analyze them.